An illustration design on Mak Inang dance step / Muhammad Al-Azeem Shamsul Bahari - Shamsul Bahari, Muhammad Al-Azeem (2018)
Malaysia has known by worldwide with its multi-culture society. Today, the Malays is Malaysia’s largest ethnic group and for the record it is counting up to 50.1% of the population (Benjamin Elisha Sawe, 7 June 2018). In Malaysia, the term of Malay refers to a person who is practice Islam and Malay Traditions, speak the Malay language and whose their ancestor are Malay. There is many to discover in Malay culture. One of them is the Traditional Malay Dance which is Mak Inang. It shows the true nature of the Malay people and the way of Malay life. This research is conducted to study the characteristic of Mak Inang and the dance steps. This descriptive study is to gain more information in understanding about the Mak Inang dance. To make this descriptive study more clearly and interesting is by doing illustration method in order to show the Mak Inang dance in Malay society. Traditional Malay dance can unifying the multiracial society in Malaysia. Other than that, the art field in performance can offers various opportunities in community. From this descriptive study, will help not just for the tourist but also for the education to the new generation and for art practitioners even more in the field of dance. Hopefully, this description will show and make the audience understand how unique and important Traditional Malay Dance especially Mak Inang dance to the Malay community and Malaysia.